Thermostabilization of Membrane Proteins by Consensus Mutation: A Case Study for a Fungal Δ8-7 Sterol Isomerase. Issue 18 (21st August 2020) - Yao, Hebang; Cai, Hongmin; Li, Dianfan
Abstract: Membrane proteins are generally challenging to work with because of their notorious instability. Protein engineering has been used increasingly to thermostabilize labile membrane proteins such as G-protein–coupled receptors for structural and functional studies in recent years. Two major strategies exist. Scanning mutagenesis systematically eliminates destabilizing residues, whereas the consensus approach assembles mutants with the most frequent residues among selected homologs, bridging sequence conservation with stability. Here, we applied the consensus concept to stabilize a fungal homolog of the human sterol Δ8-7 isomerase, a 26.4 kDa protein with five transmembrane helices. The isomerase is also called emopamil-binding protein (EBP), as it binds this anti-ischemic drug with high affinity. The wild-type had an apparent melting temperature ( T m ) of 35.9 °C as measured by the fluorescence-detection size-exclusion chromatography–based thermostability assay. A total of 87 consensus mutations sourced from 22 homologs gained expression level and thermostability, increasing the apparent T m to 69.9 °C at the cost of partial function loss. Assessing the stability and activity of several systematic chimeric constructs identified a construct with an apparent T m of 79.8 °C and two regions for function rescue. Further back-mutations of the chimeric construct in the two target regions yielded the final construct with similar apparent activity to the wild-type and an elevated T m of 88.8 °C, totaling an increase of 52.9 °C. The consensus approach is effective and efficient because it involves fewer constructs compared with scanning mutagenesis. Our results should encourage more use of the consensus strategy for membrane protein thermostabilization. Graphical abstract: Image 1 Highlights: Identification of two functional fungi homologs of the human Δ8-7 sterol isomerase. A one-step consensus mutagenesis increases the isomerase stability by 34.0 °C. Further chimeric and mutational approach increase its T m by an additional 18.9 °C. An effective and efficient strategy for membrane protein thermostabilization.